A Suspected COVID-19-associated Myocarditis Case Mimicking Life-threatening STEMI: a Shark Fin Appearance - Ratna Mariana Tamba; Andika Sitepu (Universitas Airlangga, 2021)
Some cases of myocarditis have been reported associated to Covid-19. The presence of proinflammatory response from immune cells suggested occurs by binding to membrane protein ACE-2 leading to myocardial damage. Our hospital got a refferal from a non-PCI-capable hospital with a 51-years-old woman chest pain and progressive heavy breath with history of fever two days ago. She was diagnosed with anterior STEMI and cardiogenic shock on vassopressors. Her electrocardiogram showed shark fin appearance suggesting life-threatening STEMI. Her rapid test for covid-19 are non-reactive for both IgM and IgG. Her NCCT-thorax showed ground glass opacity in both lungs. Her laboratories finding showed elevated inflammatory markers and elevated cardiac biomarker. We took her naso-oro-pharingeal swab in the same day and process her with emergency PCI. Surprisingly, her angiography showed normal coronary artery without any significant stenosis. From There was no SARS-CoV-2 detected. In myocarditis, patient can mimick the same symptoms as STEMI such as chest pain and heavy breath with elevated cardiac biomarker, but the electrocardiogram usually shows widespread concave ST-elevation with PR-segment depression. Shark fin appearance is usually seen in life-threatening STEMI. In our patient, the NCCT-thorax showed GGO suggested Covid-19 involvement. But, the first swab was negative for SARS-CoV-2. Unfortunately, the patient was discharged without doctor’s consent, so we can not process the second swab and echocardiography to evaluate the function of myocardium. We still can not confirmed this case if it is true myocarditis-associated covid-19 and how was the involvement of the myocardium creating a shark fin mimicking life-threatening STEMI.